NILAI RELIGIUS DALAM MANTRA PENGOBATAN DI DESA TALAN KABUPATEN TABALONG (RELIGIOUS VALUES IN THE HEALING PRACTICE OF TALAN VILLAGE TABALONG REGENCY) - Leha, Noor; Ismah, Ni'matul; Syakir, Akhmad (Universitas Lambung Mangkurat, 2025)
AbstractReligious Values in The Healing Practice of Talan Village Tabalong Regency. This study aims to analyze the religious values contained in healing mantras from Talan Village, Tabalong Regency. The research employs a qualitative approach with textual and contextual analysis methods. The data sources consist of five healing mantras: tawar dingin (for fever), sakit gigi (toothache), tawar racun (antidote for poison), and mandi sangga (ritual cleansing), collected through in-depth interviews and observations. The research data include words, phrases, and sentences that reflect religious values, particularly those related to the concept of tawhid (the oneness of God). The findings reveal that the healing mantras of Talan Village embody religious values rooted in tawhid, encompassing three core elements—faith (iman), piety (taqwa), and repentance (tawbah). These values serve as a medium for cultural and Islamic education within the community, especially among the younger generation, fostering an integrated understanding of culture and the fundamental principles of Islam in daily life.Keywords: religious values, healing mantra, tawhid, Banjarese culture, IslamAbstrakNilai Religius dalam Mantra Pengobatan di Desa Talan Kabupaten Tabalong. Penelitian ini bertujuan untuk menganalisis nilai religius yang terkandung dalam mantra pengobatan di Desa Talan, Kabupaten Tabalong. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis tekstual dan kontekstual. Sumber data penelitian berupa lima mantra pengobatan, yaitu mantra tawar dingin (demam), sakit gigi, tawar racun (mengobati racun), dan mandi sangga, yang diperoleh melalui wawancara mendalam dan observasi. Data penelitian berupa pada kata, frasa, dan kalimat yang mengandung nilai religius, khususnya pada aspek tauhid. Hasil penelitian menunjukkan bahwa mantra pengobatan Desa Talan memuat nilai religius pada aspek tauhid yang meliputi tiga unsur utama, yaitu iman, takwa, dan tobat, yang bermanfaat sebagai sarana edukasi budaya dan nilai Islam dalam masyarakat, khususnya generasi muda sehingga pemahaman budaya menyatu dengan nilai dasar Islam dalam kehidupan sehari-hari.Kata-kata Kunci: nilai religius, mantra pengobatan, tauhid, budaya Banjar, Islam